Improvement of obesity-induced fatty liver disease by intermittent hypoxia exposure in a murine model - Chen, Liya; Wang, Yao; Zheng, Weikun; Zhang, Hu; Sun, Yan; Chen, Yiping; Liu, Qi (Frontiers in Pharmacology, 2023)
The high prevalence of non-alcoholic fatty liver disease (NAFLD) in the world raises an important concern for human health. The western diet containing high fat and fructose is the risk factor for NAFLD development. Intermittent hypoxia (IH), known as the basis of obstructive sleep apnea (OSA), normally is correlated with impaired liver function. However, the role of IH in liver injury prevention has been revealed by many other studies based on the different IH paradigms. The current study, therefore, tests the impact of IH on the liver of high-fat and high-fructose diet (HFHFD) fed mice. Mice were exposed to IH (2 min cycle, FiO2 8% for 20s, FiO2 20.9% for 100s; 12 h/day) or intermittent air (FiO2 20.9%) for 15 weeks, with normal diet (ND) or high-fat and high-fructose diet (HFHFD). Indices of liver injury and metabolism were measured. IH causes no overt liver injury in mice fed an ND. However, HFHFD-induced lipid accumulation, lipid peroxidation, neutrophil infiltration, and apoptotic process were significantly attenuated by IH exposure. Importantly, IH exposure altered bile acids composition and shifted the hepatic bile acids towards FXR agonism, which was involved in the protection of IH against HFHFD. Taken together, these results support that the IH pattern in our model is beneficial to liver injury caused by HFHFD in experimental NAFLD.